2011
DOI: 10.1182/blood-2011-02-334565
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody blockade of IL-2 receptor α during lymphopenia selectively depletes regulatory T cells in mice and humans

Abstract: IntroductionThe alkylating chemotherapeutic agent temozolomide (TMZ) has been shown to prolong survival in patients with glioblastoma (GBM) and metastatic melanoma; however, patients with these diseases treated with TMZ possess a median survival of Ͻ 15 months. 1,2 Novel approaches are required to treat these devastating malignancies, and the exquisite specificity inherent to immunotherapy makes it an appealing option.Despite the potential of cancer immunotherapy, limited success has been achieved within this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
101
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 43 publications
2
101
2
Order By: Relevance
“…Some animal studies have indicated that TMZ may enhance antitumor immunity. 10,14,19 In a murine model of an established intracerebral tumor, vaccination-induced immunity in the setting of myeloablative TMZ, but not non-myeloablative TMZ, leads to significantly prolonged survival. 19 These data are consistent with our interesting result that the median OS in patients with Grade 3 lymphopenia was superior to that in patients with Grade 0-2 lymphopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some animal studies have indicated that TMZ may enhance antitumor immunity. 10,14,19 In a murine model of an established intracerebral tumor, vaccination-induced immunity in the setting of myeloablative TMZ, but not non-myeloablative TMZ, leads to significantly prolonged survival. 19 These data are consistent with our interesting result that the median OS in patients with Grade 3 lymphopenia was superior to that in patients with Grade 0-2 lymphopenia.…”
Section: Discussionmentioning
confidence: 99%
“…13 In animal studies, TMZ shows the potential to enhance antitumor immunity. 10,14,19 In our pilot study, AFTV combined with TMZ was used to treat 1 patient with primary GBM and 2 patients with secondary GBM. 17 All patients demonstrated pathological improvement associated with the therapy, and the adverse effects related to AFTV plus TMZ were very minor.…”
mentioning
confidence: 99%
“…This form of therapy is expected to induce both therapeutic T-cell immunity (in the form of tumor-specific effector T-cells) [47] and protective T-cell immunity (in the form of tumor-specific memory T-cells that can control tumor recurrence) [48]. Various clinical trials are currently evaluating the safety and efficacy of direct vaccination with patient-specific dendritic cells (DCs) [49,50]. Additionally, vaccination with tumor-derived peptides that rely on recruitment and activation of APCs have demonstrated potent immune responses [51–55].…”
Section: Expert Commentary: Ccl3 In Cancer Immunotherapymentioning
confidence: 99%
“…In humans, anti-CD25 antibodies such as daclizumab have been developed, but their capacity to deplete human Tregs is questioned by transplantation studies. Recent data suggest that in a mouse model of glioma monoclonal antibodies against IL-2a receptor CD25, when administered during lympho depletion caused by temozolomide, decrease the number of Tregs and increase the anti-tumor efficacy of vaccination [124]. A reduction in Treg frequency was also verified in patients receiving anti-CD25 antibodies after temozolomide-induced lymphodepletion [124].…”
Section: Brain Cancer Immunotherapy: An Overviewmentioning
confidence: 97%